ELECTRONIC AND DYNAMICAL PROPERTIES OF BULK AND LAYERED MoS2 - A. V. Krivosheeva; V. L. Shaposhnikov; V. E. Borisenko; J. -L. Lazzari (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Electronic and dynamical properties of MoS2 are determined by means of theoretical calculations. Various numbers of layers with different thickness of the vacuum layer were considered. We have found that the band gap of bulk MoS2 is increasing upon decreasing of the number of layers from 0.76 eV up to 1.85 eV, and transforms from indirect to direct one in one-monolayer structure. The influence of vacancies on the electronic properties of MoS2 is analyzed and its dynamical properties are presented.